PENGABDIAN UNTUK NEGERI MELALUI KOPERASI DENGAN APLIKASI KEUANGAN “SIKIRUN” - Tama, Annafi Indra; Sumadyo, Malikus; Rofieq, Ainur; Alrasyid, Harun; Nuryono, Rahmat (LPPM Universitas Islam 45 Bekasi, 2025)
In the era of digitalization, cooperatives in Indonesia face challenges in preparing financial reports that are accurate, efficient, and transparent. Koperasi Panca Sejahtera Bersama (KOPASMA), located in Bekasi Regency, still encounters limitations in system-based financial recording and reporting. Therefore, innovation in the form of a financial information system is required. This community service activity aims to enhance KOPASMA’s capacity through the design and implementation of a cooperative financial application, namely the Financial Information System for Cooperatives for the Nation (SIKIRUN). The implementation method includes a needs analysis, system design, application development, user training, and assistance during implementation. Additionally, to enhance the cooperative's competitiveness in the digital era, this initiative also involves digital marketing strategies, including registering KOPASMA on various e-commerce platforms such as Shopee, Tokopedia, Instagram, and WhatsApp Business, as well as developing a cooperative website to provide information to stakeholders. The documentation of this activity has been compiled into an educational video published on the institution's YouTube account to maximize its impact. Furthermore, the innovation in the design of the cooperative financial accounting system has been registered as Intellectual Property Rights (IPR) with the Ministry of Law and Human Rights of the Republic of Indonesia. The results of this activity indicate that the implementation of SIKIRUN has significantly improved the efficiency and accuracy of cooperative financial reporting. The utilization of digital platforms has also positively influenced marketing strategies and expanded the cooperative's business reach. Thus, this initiative contributes to strengthening cooperative financial governance and promoting the digital transformation of cooperatives in Indonesia.